HIV incidence, risk factors, and motivation for biomedical intervention among gay, bisexual men, and transgender persons in Northern Thailand - Suwat Chariyalertsak (2018)
Background: HIV prevalence among men who have sex with men (MSM) and transgender (TG) persons is high and increasing in Chiang Mai, northern Thailand. Objectives: To describe demographic, socioeconomic, sexual behavior and interest in future HIV prevention trials among gay and bisexual MSM and TG presenting for HIV testing (VCT) and pre-screening for the iPrEx pre-exposure chemoprophylaxis trail. Methods: In 2008-09, MSM/TG participants attending VCT were interviewed and tested for HIV and STI. Univariate and multivariate regression analyses were done to assess associations with HIV infection. Results: A total of 551 MSM clients (56.1% gay, 25.4% TG, and 18.5% bisexual (BS)) were enrolled. The mean age was 23.9 years. HIV prevalence among MSM overall was 12.9% (71/551); 16.5% among gay men, 9.3% among TG, and 6.9% among BS. Consistent use of condom was low, 33.3% in insertive anal sex and 31.9% in receptive anal sex. Interest in participation was high, 86.3% for PrEP, 69.7% for HIV vaccine trials, but 29.9% for circumcision. HIV was independently associated with being gay identified, aOR 2.8, p = 0.037 and with being aged 25-29, aOR 2.7, p = 0.027. Among repeat testers, HIV incidence was 8.2/100 PY, 95% CI, 3.7/100PY to 18.3/100PY. Conclusion: HIV risks and rates varied by self-reported sexual orientation and gender identity. HIV was associated with sexual practices, age, and being gay-identified. These are populations are in need of novel prevention strategies and willing to participate in prevention research. © 2011 Chariyalertsak et al.